The Influence of Safety Climate on Safety Performance in Loading and Unloading Companies - Setiono, Beni Agus (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2024)
Safety performance is a reflection of the occurrence of work accidents which are influenced by several factors. The purpose of this research is to explain the influence of safety climate on safety performance in loading and unloading companies. The method used in this research is a survey via questionnaires conducted on loading and unloading workers. Determining the sample of respondents used the simple random sampling method. The respondents in this study were 50 loading and unloading workers. Data analysis uses Linear Regression and hypothesis testing in this research uses the t test. The research results show that safety climate has a positive and significant effect on safety performance at loading and unloading companies.